Activation of the mTOR pathway by the amino acid (L)-leucine in the 5q- syndrome and other ribosomopathies. - Boultwood, J; Yip, B; Vuppusetty, C; Pellagatti, A; Wainscoat, J (2013)
Patients with the 5q- syndrome and Diamond-Blackfan anemia (DBA) suffer from a severe macrocytic anemia. The 5q- syndrome and DBA are disorders of aberrant ribosome biogenesis (ribosomopathies) and haploinsufficiency of the ribosomal protein genes RPS14 and RPS19, respectively, underlies the anemia found in these disorders. Erythroblasts obtained from patients with the 5q- syndrome and DBA show impaired mRNA translation and this defect in translation may represent a potential therapeutic target in these ribosomopathies. There are some indications that the amino acid l-leucine, a translation enhancer, may have some efficacy in this group of disorders. Recent studies have shown that l-leucine treatment of zebrafish and murine models of the 5q- syndrome and DBA results in a marked improvement in the anemia. l-leucine treatment of RPS14-deficient and RPS19-deficient erythroblasts and erythroblasts from patients with the 5q- syndrome has been shown to result in an increase in cell proliferation, erythroid differentiation and mRNA translation in culture. l-leucine has been shown to improve hemoglobin levels and transfusion independence in a patient with DBA. l-leucine activates the mTOR (mammalian target of rapamycin) signaling pathway that controls cell growth and mRNA translation. There is evidence to suggest that the promotion of translation via the mTOR pathway by l-leucine is the mechanism that underlies the enhanced erythroid progenitor cell growth and differentiation observed in animal and cellular models of the 5q- syndrome and DBA treated with this amino acid. These data support the rationale for clinical trials of l-leucine as a therapeutic agent for the 5q- syndrome and DBA.